RISK FACTOR ANALYSIS OF CARIES THROUGH SALIVA IN CLEFT LIP CHILDREN WITH OR WITHOUT CLEFT PLATE NON SYNDROMIC - Yayun Siti Rochmah; Anindita Dyah Palupi; Aulia Noviana; Shofwatin Ni’mah (Denta Journal Kedokteran Gigi, 2022)
Background: The number of cleft lips or palatal cases is still very high in Indonesia, the growth of cleft lips or palatal cases was 1: 700. This prevalence varies for each region in Indonesia. The condition and composition of saliva in children affect the condition of dental caries, including protein statherin, histatin -1, and calcium minerals.  Statherin has the strongest interaction with calcium hydroxyapatite, Histatin-1 has an antimicrobe and antifungal effect and calcium is an imported mineral component The purpose of this study was to analyze the children's saliva of cleft lips with or without cleft palatal non- syndromic against the risk of caries. Material and Method: This study used an Observational Analytic method with a Post Test Only Control Group Design. Saliva samples were taken by the pipetting method, saliva samples were taken from 20 children with cleft lips with or without palate and 20 normal children, aged 3-17 years, with good general health. Analysis levels of Statherin, Histatin-1, and Calcium minerals used the ELISA Method. Statistical analysis used ANOVA. Result and Discussion: The results showed that the average level of statherin for children with a cleft lip was 0.65 µg / ml, whereas for normal children was 1.1 µg / ml, the results of the analysis of histatin-1 salivary protein showed an average of 0.86 ± 0.50 at cleft children and 1.01 ± 0.71 for normal children, mean calcium levels in saliva for cleft children is 1.09 ± 0.09 mmol / L and normal children were 1.34 ± 0.13 mmol / L. ANOVA analysis for the three salivary components were found to be p = 0.001, which means that there were significant differences between the average levels of statherin, histatin-1, and calcium in cleft lips children with or without cleft palate and normal children. Conclusion: The levels of statherin, histatin-1, and salivary calcium can be early diagnostic risk dental caries in children with cleft lips/palate nonsyndromic, to optimize management of preventing dental caries on clefts cases.